Reducing OGT and O-GlcNAcylation enhance the anticancer effects of oxaliplatin in SW620 metastatic colorectal cancer cells - Thirasak Bunsuk; Juthamard Chantaraamporn; Photsathorn Mutapat; Penchatr Diskul Na Ayudthaya; Daranee Chokchaichamnankit; Chantragan Srisomsap; Jisnuson Svasti; Voraratt Champattanachai (PLoS ONE, 2026)
O -GlcNAcylation, a single attachment of N-acetylglucosamine (GlcNAc) on serine/threonine residues of nuclear-cytoplasmic proteins, is frequently upregulated in various cancers and implicated in several aspects of tumor progression. Growing evidence reports that treatments of chemotherapeutic drugs may activate protein O -GlcNAcylation. However, its precise role in modulating chemotherapeutic responses, particularly in colorectal cancer (CRC), remains poorly defined. Herein, we investigate the biological effects of oxaliplatin (OXA), a first-line chemotherapy drug for patients with metastatic CRC, and protein O -GlcNAcylation reduction in SW620 metastatic CRC cells. OXA treatment alone reduced cell viability as well as proliferation, and increased the levels of protein O -GlcNAcylation and GFPT1, the rate limiting enzyme of hexosamine biosynthetic pathway which is a nutrient sensor of glucose metabolism. Inhibition of protein O -GlcNAcylation via genetic knockdown of O -GlcNAc transferase (OGT) or chemical inhibition (OSMI-1) markedly enhanced SW620 sensitive to OXA. This was evidenced by decreased cell viability and proliferation, increased cell apoptosis, and cell cycle arrest. Mass spectrometry-based proteomics and bioinformatics analysis revealed that the combination of OGT knockdown and OXA treatment majorly downregulated several ribosomal proteins. In addition, OXA treatment and OGT knockdown altered proteins involved in critical pathways including DNA synthesome complex, glycolytic process, negative regulation of gene expression, cell cycle process, and negative regulation of protein phosphorylation. Specifically, OGT downregulated several ribosomal proteins, and OGT knockdown influenced proteins across the identified pathways. Taken together, these findings demonstrate that reducing OGT and protein O -GlcNAcylation may enhance the sensitivity of CRC cells to OXA, and the altered pathways may offer new insights into potential mechanisms for overcoming CRC chemoresistance.